METHOD OF CONTROL OF TECHNICAL CONDITION OF INSULATION OF ELECTRICAL EQUIPMENT OFTHE GENERATOR-TRANSFORMER UNIT - KUTIN, Vasil; KUTINA, Marina; SHPACHUK, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Significant wear of the main electrical equipment of the power supply scheme (synchronous generators, complete shielded power lines, transformers) of thermal and nuclear power plants, implementation of the policy of extending the service life of existing power units, and gradual implementation of equipment repair strategies according to technical condition determines the relevance of development of new and improvement of existing systems for monitoring the technical condition of electrical equipment in general and its insulation characteristics in particular. Insulation diagnostics, relay protection devices and information-measuring systems currently operated on power units do not allow tracking changes in electrical insulation parameters of electrical equipment such as insulation resistance and capacitance relative to ground and tangent angle of dielectric loss detection that makes detection of defects in isolation at an early stage of their development impossible. Relay protection devices can be insensitive to single-phase earth faults of the stator winding near the neutral and with a symmetrical decrease in the insulation parameters of the stator winding, as well as malfunction when starting units due to voltage asymmetry in generator phases. The method of control of technical condition of electrical equipment insulation in the generator-transformer unit circuit is proposed, which is based on combined superimposition of direct current and alternating current with frequency less than industrial, control of discharge of precharged capacitor and control of alternating current flow with Rogovsky coils. The proposed method will detect both abrupt and gradual changes in the technical condition of the insulation of electrical equipment of the "generator-transformer" unit, improve the quality of planning of repair work and speed up the search for faulty elements in case of damage.